The expressive body in life, art, and therapy : working with movement, metaphor, and meaning - Halprin, Daria (Jessica Kingsley Publishers, 2003)
Drawing on her extensive experience in expressive arts therapy, Daria Halprin presents a unique approach to healing through movement and art. She describes the body as the container of one's entire life experience and movement as a language which expresses and reveals our deepest struggles and creative potentials. Interweaving artistic and psychological processes, she offers a philosophy and methodology which invites the reader to consider the transformational capacity of the arts. In this essential resource for anyone interested in the integration of psychotherapy and the arts, Halprin also p.